Analysis of Transcriptome and Terpene Constituents of Scots Pine Genotypes Inherently Resistant or Susceptible to Heterobasidion annosum - Liu, Mengxia; Wang, Kai; Haapanen, Matti; Ghimire, Rajendra P.; Kivimäenpää, Minna; Asiegbu, Fred O. (Frontiers in Plant Science, 2022)
Root and stem rot caused by Heterobasidion annosum is a severe problem in boreal Scots pine. Dissecting the features of disease resistance is generally an essential step in resistance breeding in plants and forest trees. In this study, we explored inherent resistance factors of Scots pine against H. annosum. A total of 236 families consisting of 85 full-sib (FS), 35 half-sib population mix (HSpm), and 116 half-sib (HS) families of Scots pine seedlings were inoculated with a H. annosum isolate. We sampled needle tissues before inoculation for terpene measurements and RNA sequencing. Based on the lesion area, the extremes of 12 resistant and 12 susceptible families were selected for further analyses. Necrotic lesions resulting from fungal infection were in a weak to moderate relationship with the plant height. Monoterpenes were the principal terpene compounds observed in Scots pine seedlings. Concentrations of 3-carene were significantly higher in pine genotypes inherently resistant compared with susceptible seedlings. By contrast, susceptible genotypes had significantly higher proportions of α-pinene. Gene ontology analysis of differential expressed transcripts (DETs) revealed that response to biotic factors was enriched in resistant seedlings. Functional characterization of individual DETs revealed that higher expression of transcripts involved in response to abiotic stress was common in susceptible genotypes. This observation was supported by the annotation of hub genes in a key module that was significantly correlated with the lesion trait through weighted gene co-expression network analysis (WGCNA) of 16 HS and HSpm samples. These findings contribute to our understanding of constitutive resistance factors of Scots pine against Heterobasidion root and stem rot diseases.